Livros paradidáticos como mediadores do ensino de conteúdos matemáticos na Educação Básica - REIS, Geovana Natalina Rocha dos (2024)
The present work was elaborated with the intention of analyzing the importance of using paradidactic books as teaching mediators of mathematical contents in basic education from the use of the active storytelling methodology. The text presents investigations on traditional methodology and active methodologies in teaching, seeking to understand their influence on learning, presents the paradidactic book as a resource to be used in the classroom, and how it contributes to the process of knowledge construction, also talks about the importance of reading in Mathematics learning. To conclude, a teaching approach is presented that involves the use of a paradidactic book and storytelling, an active methodology, as a strategy to teach in an engaging and attractive way.